Nursing Staff Practices Regarding Infection Control Measures at Raparin Teaching Hospital for Children in Erbil City - Ramyar Mutalib Kalhury; Norhan Zeki Shaker (Hawler Medical University, 2023)
Background and objectives: Nosocomial infection is one of the main reasons of mortality and has significant financial costs due to elevated hospitalization and prognosis; thus, they should be prevented and controlled. This study aimed to assess the practice of the nursing staff regarding infection control measures at Raparin Teaching Hospital for Children. Methods: A descriptive study was conducted in Raparin Teaching Hospital for Children in Erbil City, Kurdistan Region/Iraq. A purposive sample involving 81 nurses working in emergency, ICU, NICU, and surgical units at Raparin Teaching Hospital for Children who care for children was selected for the study. The researcher developed a checklist format developed by the researcher for data collection that included three parts: socio-demographic characteristics, vaccination history, and nurses' practice regarding infection control measures. The data were processed and analyzed using Statistical Package for the Social Sciences (SPSS), version 26. Results: Most (77.8%) of the nurses were living in urban areas and they showed fair performance (81%). The results showed that 45.5% of ICU nurses outperformed their counterparts in terms of performance. The results also revealed that the younger nurses were better in terms of performance. Furthermore, the results revealed that 75.3% of the nurses have fair performance, 17.3% have good performance, and 7.4% have poor performance. Conclusion: Based on the overall performance of the nurses, most of the nurses have fair infection control practices, and the minority of them have poor practices. Younger nurses showed better performance in comparison to others.